Diversity of haemogregarine parasites infecting Brazilian snakes from the Midwest and Southeast regions with a description of two new species of Hepatozoon (Apicomplexa: Adeleorina: Hepatozoidae) - Úngari, Letícia Pereira [UNESP] (2022)
Although Brazil is a hotspot for snake species, there is a lack of information on the biodiversity of haemoparasites infecting these hosts. Thus, the present study aimed to bring new insights on the diversity of species of Hepatozoon (Apicomplexa: Adeleorina: Hepatozoidae) infecting Brazilian snakes from the Midwest and Southeast regions. The snakes were captured from 2018 to 2020 from the states of Mato Grosso, Mato Grosso do Sul, Goiás, and São Paulo. Three to five blood smears were made and the remaining blood sample was stored for further molecular analysis. Moreover, histopathological slides of the organs were stained with haematoxylin-eosin. Regarding molecular diagnosis, PCR was performed targeting different regions of the 18S rRNA gene of apicomplexan parasites. From the 13 free-living snakes screened, ten (76.92%) were found infected with Hepatozoon spp. Based on morphological and morphometric tools, five different morphotypes of species of Hepatozoon gamonts were detected. Molecular data and phylogenetic analysis support the morphological data, identifying five species of Hepatozoon from snakes, of which three species belong to previously described species, Hepatozoon cevapii, Hepatozoon cuestensis, and Hepatozoon quagliattus, with a genetic similarity of 100% (based on the 18S rRNA genetic marker). The present study identifies and describes two new species of Hepatozoon, Hepatozoon annulatum sp. nov. infecting the snake Leptodeira annulata and Hepatozoon trigeminum sp. nov. infecting the snake Oxyrhopus trigeminus. Thus, based on morphological and molecular data the present study provides new insights on haemogregarine diversity infecting Brazilian snakes from the Midwest and Southeast regions.